Apology Strategies in English: A Pragmatic Analysis of Moroccan Undergraduate EFL Learners and British Native Speakers - Khabar, Fatima Zahrae; Azhar, Adil; Latif , Hicham (International Journal of Language and Literary Studies, 2024)
The current interlanguage study investigates the realization of apologies by Moroccan EFL undergraduate students from two educational levels: semester one (S1) and semester five (S5). Their production is compared and contrasted against the apologies performed by British English native speakers. To this end, a total of 120 participants, including 40 Moroccan EFL S1 students, 40 Moroccan EFL S5 students, and 40 English native speakers, completed a written discourse completion task consisting of eight hypothetical scenarios. Adopting the mixed-method approach, data was analyzed quantitatively and qualitatively using Blum-Kulka and Olshtain’s (1984) taxonomy. The findings revealed some cross-cultural differences between the British and the Moroccan EFL respondents. In addition, the qualitative and statistical tests indicated that S5 students displayed less significant differences with English native speakers compared to S1 students in their use of apology strategies. However, only minimal progress towards native-like norms was observed.